Blue Ocean Leadership as a Transformational Strategy in Addressing Educational Challenges in Indonesia's Border Regions - Yusnaldi, Yusnaldi; Pujiati, Herni (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Indonesia's geographically challenging frontier regions. As border areas face unique educational challenges, including infrastructure limitations, teacher shortages, and cultural complexity, conventional leadership approaches often prove insufficient. Blue Ocean Leadership is a strategy that focuses on unlocking the untapped talent and motivation of employees by shifting leadership actions from traditional, competitive approaches to those that create value and inspire engagement. Drawing on blue ocean strategy principles and adaptive leadership frameworks, this research investigates how educational leaders in Indonesian border regions create uncontested leadership spaces while adapting to local contexts. Through narrative analysis of twenty-five in-depth interviews with educational leaders across five border provinces, this study identifies four transformative leadership patterns: context-sensitive innovation, cross-border collaborative networks, cultural integration in pedagogical approaches, and technology-enabled resilience. The findings reveal how adaptive leadership creates value through both structural improvements and cultural-pedagogical innovations. This research contributes to educational leadership literature by demonstrating how blue ocean leadership principles can be contextually adapted to address the distinctive challenges of border education management while building regional resilience. The study provides actionable insights for educational policymakers and practitioners in similar geopolitically complex regions worldwide.